On the Development of All-Cellulose Capsules by Vesicle-Templated Layer-by-Layer Assembly - Eivazi, Alireza (2021)
Polymeric multilayer capsules formed by the Layer-by-Layer (LbL) technique are interesting candidates for the purposes of storage, encapsulation, and release of drugs and biomolecules for pharmaceutical and biomedical applications. In the current study, cellulose-based core-shell particles were developed via the LbL technique alternating two cellulose derivatives, anionic carboxymethylcellulose (CMC), and cationic quaternized hydroxyethylcellulose ethoxylate (QHECE), onto a cationic vesicular template made of didodecyldimethylammonium bromide (DDAB). The obtained capsules were characterized by dynamic light scattering (DLS), potential measurements, and high-resolution scanning electron microscopy (HR-SEM). DLS measurements reveal that the size of the particles can be tuned from a hundred nanometers with a low polydispersity index (deposition of 2 layers) up to micrometer scale (deposition of 6 layers). Upon the deposition of each cellulose derivative, the particle charge is reversed, and pH is observed to considerably affect the process thus demonstrating the electrostatic driving force for LbL deposition. The HR-SEM characterization suggests that the shape of the core-shell particles formed is reminiscent of the spherical vesicle template. The development of biobased nano- and micro-containers by the alternating deposition of oppositely charged cellulose derivatives onto a vesicle template offers several advantages, such as simplicity, reproducibility, biocompatibility, low-cost, mild reaction conditions, and high controllability over particle size and composition of the shell.